PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PERSAMAAN GARIS LURUS MELALUI APLIKASI GOOGLE CLASSROOM - SRI TUGIYATMI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study aims to improve the mathematics learning outcomes of class VIII.A students at SMP Negeri 225 Jakarta, totaling 40 students, through the application of the Google Classroom application. The research was carried out in the odd semester of the 2021-2022 Academic Year, precisely from September to December 2021. The research method used was classroom action research which was designed in two cycles. Each cycle is carried out in four stages, namely planning, implementation, evaluation and reflection. The results of the study obtained data on student learning outcomes in the Pre-Cycle, the average value of students was only 63.25. Students who achieve completeness are students who get a score equal to or above the KKM (KKM = 75) as many as 10 students (25.00%). In Cycle I, the average value of students is 72.00. There were 25 students (62.50%) who achieved completeness. In Cycle II, students who achieved completeness were 31 students (77.50%). The results of this study indicate that there is an increase in mathematics learning outcomes by 15%. The conclusion of this study is that learning through the application of the Google Classroom application can improve mathematics learning outcomes for class VIII.A students at SMP Negeri 225 Jakarta. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar matematika peserta didik kelas VIII.A SMP Negeri 225 Jakarta yang berjumlah 40 peserta didik, melalui penerapan aplikasi google classroom. Penelitian dilaksanakan pada semester ganjil Tahun Pelajaran 2021- 2022 tepatnya bulan September sampai datang bulan Desember 2021. Metode penelitian yang digunakan adalah peneltian tindakan kelas yang dirancang dalam dua siklus. Setiap siklus dilaksanakan dalam empat tahapan yaitu perencanaan, pelaksanaan, evaluasi dan refleksi. Hasil penelitian didapatkan data hasil belajar peserta didik pada Pra Siklus, nilai rata- rata peserta didik hanya 63,25. Peserta didik yang mencapai ketuntasan yaitu peserta didik yang memperoleh nilai sama dengan atau diatas KKM ( KKM= 75) sebanyak 10 peserta didik (25,00%). Pada Siklus I , nilai rata- rata peserta didik sebesar 72,00. Peserta didik yang mencapai ketuntasan sebanyak 25 peserta didik (62,50%). Pada Siklus II , peserta didik yang mencapai ketuntasanswebanyak 31 peserta didik (77,50%). Hasil penelitian ini menunjukkan bahwa terjadi peningkatan hasil belajar matematika sebesar 15%. Kesimpulan penelitian ini adalah pembelajaran melalui penerapan aplikasi google classroom dapat meningkatkan hasil belajar matematika pada peseta didik kelas VIII.A di SMP Negeri 225 Jakarta.